Pengaruh Katekin dalam Teh Kombucha sebagai Agen Alami Antipenuaan Kulit: Reviu - Zilva Karimah Azahra (Yayasan Rahmat Islamiyah, 2023)
Catechin is secondary metabolites known as antioxidants in tea leaves and their products. One of the most popular processed tea leaves is kombucha tea, which contains catechin as antioxidants. The purpose of writing this review article is to discuss the catechins contained in processed kombucha tea as antioxidants which are believed to be used as natural agents in preventing skin aging. The collected data were then analyzed qualitatively using deductive analysis techniques by searching for reference articles through 14 databases: Sciencedirect, Researchgate, Google Scholar, Elsevier, PubMed, Emeraldinsight, Sage Research Methods, IG Library, Springer Link, MBC, MDPI, NIH, CyTA and Oxford UniversityPress. The analysis shows that kombucha tea containing these catechin is proven to have good potential and activity as an antiaging functional food. The results of investigations pertain to the effect of catechin on apoptosis induced by oxidative stress in fibroblasts which trigger skin conditions. Catechin compounds protect the skin against cell damage induced by oxidative stress in fibroblasts. Oxidative stress is the mechanism underlying skin aging because it triggers apoptosis in various cell types, including fibroblasts, which play an important role in maintaining healthy and youthful skin. It is also known that the process of tea fermentation by microorganisms in kombucha tea results in an increase of tea bioactivity, namely high antioxidants. Catechin prevent aging by inhibiting the phosphorylation of p38 and c-Jun terminal kinases (JNK). The results show that the abundance of catechin has potential as an agent for the prevention of skin aging.